Comprehensive Comparison of a New Tin-Coated Copper Mesh and a Graphite Plate Electrode as an Anode Material in Microbial Fuel Cell - Taskan, Ergin; Hasar, Halil (Springer, 2015)
This paper summarizes the comparison of a new tin-coated copper (t-coating Cu) mesh electrode with a graphite plate electrode for potential power generation and biocompatibility in a microbial fuel cell (MFC). The study, which used domestic wastewater, demonstrated that t-coating Cu mesh electrode produced a power density (271 mW/m(2)) approximately three times higher than that produced by a graphite electrode (87 mW/m(2)). Scanning electron microscopy (SEM) results revealed that bacterial morphology on the two electrodes significantly varied. The t-coating Cu mesh electrode surface had higher bacterial diversity because the open three-dimensional macro-mesh structure allowed an excellent electro-biofilm attachment. Kinetic performances evaluated using the Nernst-Monod equation demonstrated that the t-coating Cu mesh electrode had both higher power density and good biocompatibility in a large surface area, high chemical stability, and favorable metallic conductivity.
Keywords: Microbial fuel cell; Tin coating copper mesh; Graphite electrode; Power density; Biocompatibility